Interactors: operators to automatically generate interactive multimedia documents from captured media - Vega-Oliveros, Didier A.; Martins, Diogo S.; Pimentel, Maria da Graça C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2010: Proceedings of the 16th Brazilian Symposium on Multimedia and the Web, 2010)
In some scenarios, it is paramount that collaborative synchronous sessions be recorded for later review. Particularly in the case of webconferencing tools, the approach usually adopted for recording a meeting is to generate a linear video with the content of the exchanged media. Such approach limits the review of the meeting to the user watching a video using the traditional timeline-based video controls. In this work we advocate that synchronous communication tools generate interactive multimedia documents as a result of a session. For this purpose we detail the generation of an interactive multimedia document by means of user-media operators (e.g. slide changes, chat messages, ink-based interactions, audio events) that we call Interactors, enabling users to browse the generated document by navigating points of interest in the captured media. We de ne the Interactors approach and demonstrate it in the context of a tool in use.